Between structures and norms: assessing tax increment financing for the Dutch spatial planning toolkit. Issue 3 (May 2015) - Root, Liz; van der Krabben, Erwin; Spit, Tejo
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of the paper is to assess the institutional (mis)fit of tax increment financing for the Dutch spatial planning financial toolkit. By applying an institutionally oriented assessment framework, we analyse the interconnectivity of Dutch municipal finance and spatial planning structures and practices. Empirical findings from the case study highlight several insights: 1) the application of tax increment financing (TIF) would be more constrained by socio-political than technical dimensions; 2) such an instrument may not achieve the policy goal of shifting financial risk away from local government given the corporatist characteristics of Dutch planning culture; and 3) despite apparent institutional space to consider alternative instruments, enduring norms tend to be resistant to change.